Geophysical survey for groundwater potential investigation in peat land area, Riau, Indonesia. (April 2018) - Islami, N; Irianti, M; Azhar; Nor, M; Fakhrudin
Abstract: Tropical forests, especially peat lands, are particularly vulnerable to forest fires. Fires are the most common disasters in peat lands in the dry season, especially in Riau Province, Indonesia. In the process of extinguishing the peat fire, several substantial problems arise to stop peat fires during this period. This study aims to determine the possibility of using ground water as a source of water to anticipate the early mitigation of peat land fires disaster. The geoelectrical resistivity surveys were used to predict the subsurface geological data including peat thickness and depth of aquifers. The geometry of peat lands was determined using geostatistics based on geoelectrical resistivity interpretation data. Peat Land thickness varies up to 4 m in the north and is thinner to the south. A shallower and deeper aquifer is available at a depth of 13 m to 18 m and 70 m to 90 m respectively. In general, the potential of groundwater in the shallow aquifer is predicted to be sufficient for peat land watering anytime.